Effects of Cannabis on Aggressive Behaviour and Dental Health - Osuh, Jackson Iheukwumere; Osuh, Mary Ebelechukwu (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
Cannabis sativa, commonly known as cannabis, has been a subject of extensive research due to its psychoactive properties and potential therapeutic applications. Recent studies have explored its effects on various physiological and behavioural parameters, but the effects on aggressive behaviour and dental health remains under-investigated. This study aims to address this gap by examining the effects of different dosages of cannabis on aggressive behaviour and dental health in albino rats.A total of 80 albino rats were used in this study, divided into four experimental groups: 10 mg cannabis, 20 mg cannabis, 50 mg cannabis, and a placebo group. Each group consisted of 10 males and 10 females. The rats were administered their respective dosages of cannabis or placebo daily for a period of 4 weeks. Aggressive behaviour was assessed using standardized behavioural tests, including the Resident-Intruder Test and the Aggression Test. Dental health was evaluated by examining the presence of dental plaque, gingival inflammation, and tooth decay using the Modified Community Periodontal Index (CPI). A two-way ANOVA was employed to analyze the result. The analysis revealed a significant dose-dependent increase in aggression and deterioration in dental health with higher cannabis doses (p < 0.001). Specifically, animals administered the highest dose exhibited the most severe aggressive behaviour and dental issues, including increased plaque accumulation and gum inflammation. Gender was found to significantly influence aggressive behaviour, with males showing higher aggression compared to females (p < 0.01). However, gender did not significantly affect dental health (p = 0.268), and the interaction between cannabis dose and gender was not significant for either outcome (p = 0.798).The findings indicate that higher doses of cannabis exacerbate both aggressive behaviour and dental health deterioration in an animal model. While aggression is influenced by gender, the adverse effects on dental health are consistent across sexes. There is the need for further research on the long-term effects of cannabis and suggestion that public health measures should address both behavioural and dental health risks associated with cannabis use.